A Study Of The Usage Of Goat Milk Among Multicultural Malaysians: Its Mediating Factors Towards Knowledge, Attitude, Practice (Kap) And Effectiveness Of The Intervention - Lim Lee Chang
Goat milk is one of the healthy natural foods, however its functional and nutritional value is less disseminated across consumers. This study aimed to determine goat milk consumption intention, knowledge, attitude, and practice (KAP) among multicultural Malaysians, and the effectiveness of an intervention programme to increase the KAP towards goat milk. The Stage 1 study was a quantitative research design that gave detailed description on consumers’ consumption intention. Using self-administered questionnaires, data was collected from 423 respondents selected via probabilistic cluster sampling at Giant hypermarkets in Klang Valley. This stage aimed to study whether relationship exists between attitude, social influence, and self-efficacy on goat milk consumption among consumers to get meaningful implications on improving the goat milk consumption. Data was analysed using SmartPLS. In Stage 2 cross-sectional KAP study, respondents were selected using multistage sampling method to represent equal samples of different ethnics’ distribution in Malaysia. Self-administered questionnaires were distributed at randomly selected Giant hypermarkets. A total of 398 people took part in the survey. The SPSS v25.0 was used to analyse the data. Nutrition education intervention programme was conducted in Stage 3. Using the randomized controlled trial (RCT) design, 58 participants from USIM and KUTAR participated in the 8-weeks intervention programme. The study found an association between consumer attitude and self-efficacy towards goat milk consumption. The mediation effect of health consciousness indicated that consumers considered the benefits of goat milk in their readiness to consume goat milk. About 53% of respondents (n=211) had good knowledge on goat milk health benefits while 45.2% (n=180) had favourable attitude toward drinking goat milk. For the past one year, 53.8% (n=214) consumed goat milk. Among ethnicities, the Malay ethnic showed significantly higher mean knowledge (3.98±0.572) and attitude (3.84±0.625) than the rest. There was no significant mean difference in practice on goat milk among ethnics (p=0.503). In Stage 3, paired t-test showed no significant mean difference between pre and post-intervention for the control group. Intervention group showed significant improvement in their knowledge (t (57) = 8.484, p=0.000, d=1.114), attitude (t (57) = 8.414, p=0.000, d=1.105), and practice (t (57) = 4.316, p=0.000, d=0.567). This study concluded that attitude, self-efficacy, and health consciousness influenced the intention to consume goat milk. The Malay ethnic showed the highest level of KAP scores, likely due to the background of the religion that emphasizes on the way of the Prophet Muhammad in daily life including food choices. Lastly, nutrition education intervention showed promising success at increasing the KAP towards goat milk.